Allele frequencies and genotype distribution of three metformin transporter polymorphisms in Mexican population and their application in pharmacogenomics of type 2 diabetes - Chávez-Arreola, Oscar I.; Lazalde, Brissia; López-López, Marisol; Ortega-Vázquez, Alberto; Torres-Salazar, Quitzia L. (Frontiers in Pharmacology, 2024)
Background Metformin is the first-line antidiabetic therapy for type 2 diabetes in Mexico, despite recent recommendations highlighting alternatives like GLP-1 receptor agonists for individuals with obesity. Metformin elimination is reliant on liver and kidney function, and variants in transport proteins such as Multidrug and Toxin Extrusion Protein 1 (MATE1), MATE2, and Organic Cation Transporter 2 (OCT2) can influence its pharmacokinetics. Understanding these variants’ frequencies in the Mexican population is crucial for tailoring personalized treatment strategies. Objective This study aimed to determine the genotypic and allelic frequencies of key variants in metformin transporters within a Mexican population, addressing the interindividual variability in drug response. Methodology Genetic analysis was conducted on 101 healthy, unrelated Mexican subjects who were genotyped for the MATE1, MATE2, and OCT2 variants using allele-specific real-time PCR assays. Results The allele frequencies were 0.07 for OCT2, 0.23 for MATE1, and 0.67 for MATE2. The g.–66T→C variant was found only in wild-type and heterozygous forms. Comparative analysis indicated significant differences in allele frequencies between this Mexican population and other ethnic groups, highlighting potential implications for metformin efficacy and safety. Conclusion This study provides crucial insights into the genetic variability of metformin transporter genes in a Mexican population, offering a foundation for personalized therapeutic approaches in type 2 diabetes management.